Hematopoietic cell-derived RELMα regulates hookworm immunity through effects on macrophages. Issue 4 (10th July 2018) - Batugedara, Hashini M; Li, Jiang; Chen, Gang; Lu, Dihong; Patel, Jay J; Jang, Jessica C; Radecki, Kelly C; Burr, Abigail C; Lo, David D; Dillman, Adler R; Nair, Meera G
Abstract: Resistin-like molecule α (RELMα) is a highly secreted protein in type 2 (Th2) cytokine-induced inflammation including helminth infection and allergy. In infection with Nippostrongylus brasiliensis ( Nb ), RELMα dampens Th2 inflammatory responses. RELMα is expressed by immune cells, and by epithelial cells (EC); however, the functional impact of immune versus EC-derived RELMα is unknown. We generated bone marrow (BM) chimeras that were RELMα deficient (RELMα −/ − ) in BM or non BM cells and infected them with Nb . Non BM RELMα −/− chimeras had comparable inflammatory responses and parasite burdens to RELMα +/+ mice. In contrast, both RELMα −/− and BM RELMα −/− mice exhibited increased Nb -induced lung and intestinal inflammation, correlated with elevated Th2 cytokines and Nb killing. CD11c + lung macrophages were the dominant BM-derived source of RELMα and can mediate Nb killing. Therefore, we employed a macrophage-worm co-culture system to investigate whether RELMα regulates macrophage-mediated Nb killing. Compared to RELMα + /+ macrophages, RELMα −/− macrophages exhibited increased binding to Nb and functionally impaired Nb development. Supplementation with recombinant RELMα partially reversed this phenotype. Gene expression analysis revealed that RELMα decreased cell adhesion and Fc receptor signaling pathways, which are associated with macrophage-mediated helminth killing. Collectively, these studies demonstrate that BM-derived RELMα is necessary and sufficient to dampen Nb immune responses, and identify that one mechanism of action of RELMα is through inhibiting macrophage recruitment and interaction with Nb . Our findings suggest that RELMα acts as an immune brake that provides mutually beneficial effects for the host and parasite by limiting tissue damage and delaying parasite expulsion. Employing hookworm infection of RELMα −/− bone marrow chimeras, co-culture assays, and gene expression analysis, we show that lung macrophage-derived RELMα downregulates inflammation and parasite killing.